2009
DOI: 10.1186/1475-2875-8-133
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for malaria deaths in Jalpaiguri district, West Bengal, India: evidence for further action

Abstract: Background: In 2006, a cluster of malaria deaths in the highly endemic Jalpaiguri district, West Bengal, India, led to assignment of additional resources. Malaria deaths decreased, but continued to occur. A study was conducted to identify the risk factors for residual malaria deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 6 publications
1
21
0
2
Order By: Relevance
“…3 ). Access to treatment is also an important indicator of the decrease in malaria mortality and needs to reach remote communities which have an increased risk of malaria infection [ 11 , 27 ]. This study has also shown that households at greater distances from health facilities had an increased risk of malaria mortality; although there was no statistical evidence, the estimated odds ratio was substantially higher than 1 in both HDSS site.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). Access to treatment is also an important indicator of the decrease in malaria mortality and needs to reach remote communities which have an increased risk of malaria infection [ 11 , 27 ]. This study has also shown that households at greater distances from health facilities had an increased risk of malaria mortality; although there was no statistical evidence, the estimated odds ratio was substantially higher than 1 in both HDSS site.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Bangladesh has shown higher rates of malaria prevalence in children, whereas another in the neighbouring state West Bengal showed highest case fatality rate among children under five [12,28]. Children under five years are found to be more vulnerable to malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Otros factores que determinan la presencia de la enfermedad, como la colonización y la migración de la población, la ocupación, la pobreza, el analfabetismo, las creencias y prácticas de la comunidad sobre la enfermedad, la desnutrición, la falta de acceso al diagnóstico y al tratamiento, y el desarrollo de los servicios de atención, así como la disponibilidad y la oportunidad del tratamiento, pueden contribuir con la mortalidad por paludismo (19)(20)(44)(45)(46)(47)(48)(49)(50)(51).…”
Section: Resultsunclassified
“…Los conflictos sociales y los problemas de orden público que generan desplazamiento de la población, el cambio climático, la deficiente implantación de intervenciones operativas y la poca accesibilidad geográfica, aumentan la vulnerabilidad en estas áreas y producen diferentes niveles de riesgo (15,16). Igualmente, el comienzo del tratamiento luego de 48 horas de iniciados los síntomas, las demoras en la admisión en los servicios de salud y las fallas en la atención de los pacientes, son algunos de los factores identificados que se asocian con la mortalidad por paludismo (18)(19)(20)(21).…”
unclassified